A Review of Innovative Approaches to Overcoming Agricultural Extension Challenges: A Case Study of the Knowledge Gap in Kigezi Sub-Region, Uganda - Kobusiingye, Florah; Ssembatya, Richard; Kaggwa, Fred; Hambinka, Annabella (International Journal for Multidisciplinary Research (IJFMR), 2024)
Agriculture remains the backbone of Uganda’s economy, but the Kigezi region continues to face significant challenges that limit its agricultural productivity. Farmers in this region, despite their reliance on agriculture, often struggle with low yields and limited access to modern farming techniques. These challenges are exacerbated by a knowledge gap in agricultural extension services, largely caused by logistical issues, poor infrastructure, and limited access to technology. This review examines the agricultural extension challenges in Kigezi and explores innovative approaches, with a particular focus on mobile-based teaching-learning frameworks (TLFs). The article evaluates the potential of mobile technology to address these challenges by providing scalable, accessible, and context-specific solutions. The findings suggest that while Kigezi faces digital and infrastructure barriers, mobile solutions tailored to local needs could empower farmers and enhance agricultural productivity. This review aims to contribute to ongoing discussions on agricultural extension in resource-constrained regions and provides practical recommendations for bridging the extension gap through innovative mobile platforms.
Keywords: Innovative Approaches; Agricultural extension; Knowledge gap; Kigezi region